Mascot: An alternate method to prevent the misuse of visual assets in Indonesia's Covid 19 prevention campaign - Paku Kusuma; Dharsono Dharsono; Martinus Dwi Marianto; Guntur Guntur (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2022)
This article discusses the use of visual assets during the covid-19 pandemic in Indonesia. There are regulations related to restrictions on movement for everyone during the pandemic, and there is much confusion in information, resulting in information chaos, and one of the reasons is the inappropriate use of visual assets as a medium for the Covid-19 prevention campaign in Indonesia. This study aims to identify the misuse of these visual assets. This study uses visual data spread on social media and observation to examine billboards, banners, and the like scattered in the community. In addition to visual data, interviews were also conducted with graphic designers. The questions asked were about the reasons for determining the design and their motivation in utilizing visual assets. The analysis is carried out by building relationships between the designs created, the use of visual assets, and contextual relationships with other interests outside the substance of the Covid 19 prevention campaign program in Indonesia. The results of the study show that visual assets are not used proportionally in conveying the Covid-19 prevention campaign in Indonesia. The conclusion is that there is no policy that provides direction regarding the provisions for the use of visual assets in preventing the Covid-19 health disaster in Indonesia. This research contributes to the government because this research finds a rule model for the use of visual assets in Indonesia